2009
DOI: 10.1016/j.rvsc.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Transient inhibition of foot-and-mouth disease virus replication by siRNAs silencing VP1 protein coding region

Abstract: Foot-and-mouth disease virus (FMDV) is the causative agent of foot-and-mouth disease, a severe, clinically acute, vesicular disease of cloven-hoofed animals. RNA interference (RNAi) is a mechanism for silencing gene expression post-transcriptionally that is being exploited as a rapid antiviral strategy. To identify efficacious small interfering RNAs (siRNAs) to inhibit the replication of FMDV, candidate siRNAs corresponding to FMDV VP1 gene were designed and synthesized in vitro using T7 RNA polymerase. In rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In fact, VP1, VP4, 3D, 2B, 5′NCR, VPg, or 3′NCR have been previously selected as RNAi target genes [6], [12], [13], [14], [15], [16], [17], [18]. If there are conserved regions of viral genes among different serotypes of FMDV, the viral genes could be screen as RNAi targets, so we choose RNAi-VP2, RNAi-VP3, RNAi-VP4 as target site in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, VP1, VP4, 3D, 2B, 5′NCR, VPg, or 3′NCR have been previously selected as RNAi target genes [6], [12], [13], [14], [15], [16], [17], [18]. If there are conserved regions of viral genes among different serotypes of FMDV, the viral genes could be screen as RNAi targets, so we choose RNAi-VP2, RNAi-VP3, RNAi-VP4 as target site in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is a highly specific tool to down-regulate gene expression [11] and has been extensively utilized to inhibit FMDV in vitro and/or in vivo [6], [12], [13], [14], [15], [16], [17], [18]. Furthermore, transgenic mice expressing FMDV targeting shRNA was much more resistant to viral infection, as evidenced by minor abnormal pathology, as compared to the control mice after challenge with FMDV [19].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, when cells were treated with siRNAs mixtures, in addition to individual siRNAs the results demonstrated that the inhibitory effects of the mixtures on foot and mouth disease virus (FMDV) RNA replication and viral titer were approximately same as that of individual component siR-NA [39]. They suggested that mixtures did not exert significant inhibitory effect because each siRNA of the mixture might possess equal efficacy to inhibit replication of FMDV.…”
Section: Discussionmentioning
confidence: 99%
“…Specific gene silencing also can be triggered in mammalian cells by using synthetic short interfering RNA (siRNA), and plasmid or virus-mediated short hairpin RNA (shRNA). These RNAi strategies have been used successfully for suppressing the replication of human and animal viruses, including hepatitis B virus (HBV) (Kayhan et al, 2007), human immunodeficiency virus type (HIV) (Coburn and Cullen, 2002), porcine reproductive and respiratory syndrome virus (PRRSV) (Luo et al, 2013) and foot-and-mouth disease virus (FMDV) (De los Santos et al, 2005;Lv et al, 2009;Xu et al, 2012). Furthermore, we and others reported that transgenic animals expressing shRNA against virus genes showed a significant resistance to viral challenge (Pengyan et al, 2010;Li et al, 2014;Daniel-Carlier et al, 2013;Du et al, 2014).…”
Section: Introductionmentioning
confidence: 99%